Prenatal Exposure to Traffic Pollution. Issue 1 (January 2015) - Fleisch, Abby F.; Rifas-Shiman, Sheryl L.; Koutrakis, Petros; Schwartz, Joel D.; Kloog, Itai; Melly, Steven; Coull, Brent A.; Zanobetti, Antonella; Gillman, Matthew W.; Gold, Diane R.; Oken, Emily
<x xml:space="preserve">Abstract</x> Background: Prenatal air pollution exposure inhibits fetal growth, but implications for postnatal growth are unknown. Methods: We assessed weights and lengths of US infants in the Project Viva cohort at birth and 6 months. We estimated 3rd-trimester residential air pollution exposures using spatiotemporal models. We estimated neighborhood traffic density and roadway proximity at birth address using geographic information systems. We performed linear and logistic regression adjusted for sociodemographic variables, fetal growth, and gestational age at birth. Results: Mean birth weight-for-gestational age z-score (fetal growth) was 0.17 (standard deviation [SD] = 0.97; n = 2, 114), 0- to 6-month weight-for-length gain was 0.23 z-units (SD = 1.11; n = 689), and 17% had weight-for-length ≥95th percentile at 6 months of age. Infants exposed to the highest (vs. lowest) quartile of neighborhood traffic density had lower fetal growth (−0.13 units [95% confidence interval (CI) = −0.25 to −0.01]), more rapid 0- to 6-month weight-for-length gain (0.25 units [95% CI = 0.01 to 0.49]), and higher odds of weight-for-length ≥95th percentile at 6 months (1.84 [95% CI = 1.11 to 3.05]). Neighborhood traffic density was additionally associated with an infant being in both the lowest quartile of fetal growth and the highest quartile of 0- to 6-month weight-for-length gain (Q4 vs. Q1, odds ratio = 3.01 [95% CI = 1.08 to 8.44]). Roadway proximity and 3rd-trimester black carbon exposure were similarly associated with growth outcomes. For 3rd-trimester particulate matter (PM2.5), effect estimates were in the same direction, but smaller and imprecise. Conclusions: Infants exposed to higher traffic-related pollution in early life may exhibit more rapid postnatal weight gain in addition to reduced fetal growth.